Neuromuscular plantar flexor performance of sprinters versus physically active individuals - Crotty, E. D.; Furlong, L. A. M.; Harrison, A. J. (Medicine & Science in Sports & Exercise, 2024)
Introduction Comparison of the neuromuscular performance of different athlete types may give insight into the in vivo variability of these measures and their underpinning mechanisms. The study aims to compare the neuromuscular function of the plantar flexors of sprinters and physically active individuals to assess any differences in explosive force performance.